Correlation Mothers’ Knowledge about Stunting and Exclusive Breastfeeding Behavior - Syipa Izzati Hermawan; Desy Indra Yani; Henny Yulianita; Laili Rahayuwati (Journal of Nursing Care, 2023)
Stunting is still a nutritional health problem in children that has received the attention of the developing world. Knowledge of stunting plays a role in efforts to prevent stunting. Breastfeeding in the first six months of life is one of the preventive behaviours whose success is influenced by knowledge. This research aimed to determine the relationship between stunting knowledge and exclusive breastfeeding behaviour in mothers with toddlers. This research design is secondary research with quantitative correlational methods with a retrospective approach. The sample was determined through a purposive sampling technique with the inclusion criteria of mothers with toddlers and exclusion criteria for mothers with children over five years old so that 55 respondents were obtained. The instrument includes demographic information, stunting knowledge, and exclusive breastfeeding behaviour. The statistical test used is Chi-Square. The study results show no relationship between the level of knowledge about stunting and exclusive breastfeeding behaviour (p-value = 0.16). Knowledge can affect the occurrence of the behaviour, but other aspects can influence the occurrence of a behaviour. Further research is needed by modifying the methods and variables used.